2022
DOI: 10.1007/s00018-022-04229-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective cleavage of ncRNA and antiviral activity by RNase2/EDN in THP1-induced macrophages

Abstract: RNase2 is the member of the RNaseA family most abundant in macrophages. Here, we knocked out RNase2 in THP-1 cells and analysed the response to Respiratory Syncytial Virus (RSV). RSV induced RNase2 expression, which significantly enhanced cell survival. Next, by cP-RNAseq sequencing, which amplifies the cyclic-phosphate endonuclease products, we analysed the ncRNA population. Among the ncRNAs accumulated in WT vs KO cells, we found mostly tRNA-derived fragments (tRFs) and second miRNAs. Differential sequence c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Additionally, some key up-regulated genes are related to SARS-CoV-2 infection ( Table S1 ). For example, ribonuclease A family member 2 (RNASE2) exhibits anti-viral capacity [ 32 ]; the up-regulation of thioredoxin domain containing 5 (TXNDC5) is induced by hypoxia [ 33 ]; marginal zone B and B1 cell-specific protein (MZB1) is involved in humoral immunity up-regulation in lung regional lymph nodes of severe COVID-19 patients [ 34 ]; lactotransferrin (LTF) displays anti-inflammatory capacity, and competes for binding receptors with SARS-CoV-2 [ 35 ]. Such intense activation of immune-related genes is the major response of severe patients to SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some key up-regulated genes are related to SARS-CoV-2 infection ( Table S1 ). For example, ribonuclease A family member 2 (RNASE2) exhibits anti-viral capacity [ 32 ]; the up-regulation of thioredoxin domain containing 5 (TXNDC5) is induced by hypoxia [ 33 ]; marginal zone B and B1 cell-specific protein (MZB1) is involved in humoral immunity up-regulation in lung regional lymph nodes of severe COVID-19 patients [ 34 ]; lactotransferrin (LTF) displays anti-inflammatory capacity, and competes for binding receptors with SARS-CoV-2 [ 35 ]. Such intense activation of immune-related genes is the major response of severe patients to SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…ANG cleavage is mainly discussed here, but other concomitant pathways have been described. For instance, Dicer cleaves tRNAs into miR-like fragments (tRFs) [63] , [64] and another Dicer- and ANG-independent pathways have been reported [2] , [7] , [65] . These multiple and overlapping tRNA cleavage pathways create an impressive number of tRNA-derived small RNAs, thus appealing for more detailed characterization.…”
Section: Discussionmentioning
confidence: 99%
“…RNases play a key role in immune defense, since it is well known their engagement in the protection of cells and organisms from microbes, especially viruses. Interestingly, Boix and coworkers recently found that RNase2 exerts its antiviral activity, in a cell line of human macrophages, by cleaving tRNAs and other ncRNA species [ 60 , 155 ].…”
Section: Rnases and Rna Processing As Tumor And Viral Infection Manag...mentioning
confidence: 99%